Edukasi Perhitungan Zakat Dalam Ekonomi Islam Untuk Mewujudkan Pemahaman Ekonomi Islam - Asia A. Yanju; Valentina Monoarfa; Saila Darban (Mopolayio : Jurnal Pengabdian Ekonomi, 2026)
Zakat is one of the important instruments in the Islamic economic system that plays a role in improving social welfare and reducing economic inequality in society. However, many people still lack a proper understanding of zakat, especially regarding the calculation of zakat al-mal such as trade zakat and income zakat. Therefore, this community service activity aims to improve public understanding of zakat calculation within the framework of Islamic economics through educational activities. The program was conducted in Pentadio Barat Village, Telaga Biru District, using a participatory education method which includes lectures, discussions, and zakat calculation simulations. The results show that there was an increase in community understanding regarding the concept of zakat, types of zakat, and proper zakat calculation in accordance with Islamic law. Furthermore, the educational activity also provided broader insights into the importance of zakat as an instrument in the Islamic economic system to achieve social justice and community welfare. Thus, zakat calculation education is expected to enhance zakat literacy and encourage people to fulfill their zakat obligations correctly.